Личность на пути к самореализации - Самарчян, Александр (Լիմուշ հրատ.)
Personality can be represented as an outcome of the impact of two processes that are unfolding simultaneously, and are mutually complementary and, in a sense, oppositely directed, viz . socialization and individualization. The former is in charge of the person’s mastering of the world around him and of the internalization of values and norms of the social environment. The latter is responsible for the uncovering and development of propensities and abilities. The personality’s proper functioning is ensured only if neither of those processes is unfolding at the expense of the other.
Keywords: Философия